POLITICAL MOBILIZATION AND INSTITUTIONAL TRUST IN LATIN AMERICA: Citizens in defense of democracy? - Barros, Marilene (EVOCATIO: Revista luso-brasileira de Filosofia, Artes e Cultura - ISSN: 2965-4254, 2023)
In this paper, I explore the important link between citizens’ political mobilization, distrust in institutions and perceptions of democracy’s effectiveness. In particular, I look at the paradoxical relation between citizens’ membership in political associations, intense distrust in institutions and quite stable evaluations of democracy in eight Latin American nations (Chile, Peru, Venezuela, Brazil, Argentina, Mexico, Dominican Republic).[1]. Intuitively, one may posit that there is a reciprocal link between these three processes, with political participation having a positive impact on perceptions of democracy, while institutional distrust would have a negative impact. Using data from the World Values Survey 95/97, I use simultaneous equation modeling to uncover the nature and extent of the relationship between the three variables, allowing me to arrive at preliminary conclusions about the main objectives of this paper: testing the hypothesis that participation and lack of institutional trust have a positive and negative impact, respectively, on citizens’ evaluation of democracy. This technique also makes possible an analysis of mediating effects of other variables on citizens’ perception of democracy as an effective or non-effective political system.